Redesign your library website - Wittmann, Stacy Ann; Stam, Julianne (Libraries Unlimited, 2016)
"A comprehensive guide for all sizes of libraries, this book guides you through the entire process of effectively redesigning your library's website--from evaluating your current site and understanding user needs, to creating a budget, through to launching and maintaining your updated site. Presents an approachable, complete guide that covers all steps in the process of revamping a library website, turning a potentially daunting challenge into a doable project, even for those without technical backgrounds. Describes various ways of handling specific steps for different sizes and types of libraries--from a 'DIY' approach to cost-effective ways of hiring outside professionals. Provides an invaluable resource for librarians and library staff members charged with the task of designing or redesigning their library's website as well as for web developers and designers who work with libraries"--Provided by publisher.